2018
DOI: 10.1097/paf.0000000000000357
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Injuries in Drowning Cases

Abstract: Discovery of bruises in the muscles of the neck and a fracture of the hyoid bone in a body recovered from water makes the diagnosis and the determination of the manner of death difficult.The aims of this work are to report a case of a drowned body with cervical injuries and to highlight the importance of interpreting these findings accurately.A 39-year-old woman was found dead face down in a 6-m deep well with a 3-m water level. She was mentally disturbed and had a history of suicide attempts. In fact, she had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The hyoid bone is protected by these structures from direct impact [6,7]. Although it does not directly make a joint, the hyoid is a sensitive bone to which the cervical and tongue muscles are attached [2,8]. The hyoid's omnidirectional mobile capacity, between the jaw and cervical spine, contributes to the less likelihood of its fracture [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The hyoid bone is protected by these structures from direct impact [6,7]. Although it does not directly make a joint, the hyoid is a sensitive bone to which the cervical and tongue muscles are attached [2,8]. The hyoid's omnidirectional mobile capacity, between the jaw and cervical spine, contributes to the less likelihood of its fracture [9].…”
Section: Discussionmentioning
confidence: 99%
“…in Canada for a 13-year-old male taekwondo athlete after experiencing a kick in the anterior neck during a match [3]. Boussaid et al reported a case of hyoid bone fracture found incidentally during an autopsy of a woman who was found dead face down in a six-meter-deep well [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation